A Chemiluminescent Immunoassay for Osteocalcin in Human Serum and a Solution to the “Hook Effect” - Shuang Han; Yifeng Xue; Junlan Zhang; Jianrong Huang; Xiuxia Liu; Yankun Yang; Zhonghu Bai; Chunxin Wang (Journal of Analytical Methods in Chemistry)
A chemiluminescent immunoassay for human serum osteocalcin, or bone Gla protein, was established using a double-antibody sandwich model. Examination of the hook effect revealed that it was significantly reduced, and no hook effect was observed at an osteocalcin concentration of 4000 ng/mL. The established method showed good analytical performance and thermal stability. The limit of detection was 0.03 ng/mL. The intra-assay coefficient of variation (CV) was 3.22%–5.64%, the interassay CV was 4.42%–7.25%, and the recovery rate was 93.22%–107.99%. Cross-reactivity (CR) was not observed with bovine, rat, mouse, rabbit, or porcine samples. The developed method showed a good correlation with the N-MID product from Roche. In total, 1069 clinical patient samples were measured using the reagent kit developed in this study.